The Effect of Communication Quality, Organizational Culture, And Team Performance on Employee Work Productivity (Case Study: Trusmi Group) - Alisya Azzahra; Editya Nurdiana (Greenation Research & Yayasan Global Resarch National, 2026)
Employee productivity is a critical indicator in determining an organization's success in achieving its strategic objectives, particularly in an increasingly competitive business landscape. Productivity is influenced not only by individual capabilities but also by organizational factors such as communication quality, organizational culture, and team performance. This study aims to analyze the influence of communication quality, organizational culture, and team performance on employee productivity at Trusmi Group. This research employs a quantitative approach with an associative method. Data were obtained through the distribution of questionnaires to Trusmi Group employees as the research respondents. Data analysis was conducted using multiple linear regression to determine the partial and simultaneous effects between variables. The results are expected to contribute to the management of Trusmi Group in formulating strategies to enhance productivity through strengthened internal communication, the development of a positive organizational culture, and the optimization of teamwork. Furthermore, this study is expected to serve as a reference for future research and for other organizations in managing internal factors that affect employee productivity.